The Transformation of Ahmadiyya Religious Education in Responding to Modernity and Social Change in the West - Sabran Kamal (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study examines the historical development, doctrinal foundations, and contemporary influence of the Ahmadiyya Movement in the modern Western world from historical and theological perspectives. The emergence of Ahmadiyya in late nineteenth-century British India represented one of several Islamic reform movements responding to colonial domination, religious polemics, and socio-political transformation. While the movement has expanded significantly across Europe, North America, and other regions through missionary activities, educational institutions, and humanitarian initiatives, its doctrinal interpretations concerning prophethood, the Promised Messiah, divine revelation, and jihad have generated sustained theological debates within the broader Muslim community. Previous studies have generally examined Ahmadiyya either as a historical movement, a missionary organization, or a theological phenomenon, with relatively limited efforts to integrate these dimensions into a comprehensive analytical framework. Employing a qualitative library research design, this study analyzes historical documents, classical and contemporary theological literature, scholarly publications, and relevant primary sources concerning the Ahmadiyya Movement. The findings indicate that the movement's expansion in the modern Western world has been facilitated by systematic missionary strategies, global migration, effective organizational structures, and the utilization of modern communication technologies. Furthermore, the study demonstrates that the movement has contributed to discussions concerning religious identity, interfaith dialogue, religious freedom, and the public representation of Islam in Western societies, while simultaneously remaining the subject of significant theological disagreement among many Muslim scholars regarding several core doctrinal issues. The novelty of this research lies in its integrative analysis that combines historical development, doctrinal examination, global expansion, and contemporary social influence within a single analytical framework. The study contributes to the fields of Islamic theology, Islamic history, religious studies, and contemporary discussions concerning Islam in pluralistic societies.